Pregnancy and antiphospholipid antibody - Lockshin, M. D.; Sammaritano, L. R. (Hämostaseologie, 2001)
The antiphospholipid antibody syndrome is defined by anticardiolipin antibody or lupus anticoagulant and recurrent pregnancy loss or recurrent thrombosis. Approximately one-third of patients with systemic lupus erythematosus, 10-15% of women with recurrent fetal loss, and 1-2% of normal women have one or both of these antibodies. The true antigen is a phospholipid-binding protein, β2-glycoprotein I, not cardiolipin. Risk for pregnancy loss is determined by IgG isotype titer, and prior pregnancy history. Early pregnancy is often normal, but placental insufficiency produces slowed fetal growth and second trimester fetal demise. The most likely mechanism is unimpeded thrombosis within the placental circulation, possibly because antiphospholipid antibody competes with placental anticoagulant I. Heparin in subanticoagulant doses plus low dose aspirin results in fetal survival rates of over 90%. Post partum, the long-term risk of maternal arterial or venous thrombosis is high.
Keywords: Antiphospholipid antibody; lupus anticoagulant; pregnancy loss; lupus